Parents' attitudes towards male teacher work in kindergarten (Journal of the College of Basic Education, 2025)
The current research aims to know the attitude of parents towards men working as teachers in kindergartens. The researcher adopted the descriptive survey approach, prepared a scale consisting of (23) paragraphs and applied it to a sample of (200) individuals from parents of children after subjecting it to validity and reliability standards. The following statistical methods were used: frequencies and percentages, Pearson correlation coefficient, Cronbach's alpha coefficient, arithmetic mean, t-test for two independent samples, one-way analysis of variance. The research results concluded that the number of parents who do not support men working in kindergartens was (104) at a rate of (52%), while those who support it numbered (96) at a rate of (48%). The tendency of parents' responses was to agree with the positives of men working in kindergartens, and tended to be (indifferent) towards the negatives of men working as teachers in kindergartens. As for knowing the extent of statistical significance in parents' attitudes attributed to personal variables, there were no statistically significant differences according for the gender variable (males and females), it was found that there were statistically significant differences according to the age variable in favor of the age group (35-40). There were also statistically significant differences according to the educational attainment variable in favor of the group whose educational attainment is a bachelor’s degree. In light of the research results, the researcher prepared a set of recommendations and proposals related to the subject related to the subject.